ENTREPRENEURIAL INTENTION AND LIMITING FACTORS IN THE EXECUTION OF BUSINESS IDEAS IN THE POPULATION OF SAN PEDRO SULA, HONDURAS - Sánchez Sauceda, Dariana Lizeth; Jeer Bendeck, Shady Ricardo; Padilla-Sánchez, Gissel; Díaz Barrientos, José María (LACCEI, 2025)
The present study aimed to identify the factors that limit the execution of business ideas in people with entrepreneurial intentions in San Pedro Sula. To do this, a quantitative approach of descriptive correlational scope with a non-experimental and cross-sectional design was used, applying a questionnaire to 302 residents over 18 years of age. The data were analyzed in SPSS using Pearson Chi Square tests to evaluate associations between demographic characteristics, training, and entrepreneurial intention. The results indicated that the most limiting internal factors are fear of failure (23%), lack of knowledge in administration (15%) and anxiety in decision-making (11%), while external factors include limited access to financing (22%), citizen insecurity (22%) and the complexity of legal procedures (37%). It was observed that the perception of preparation was the variable most strongly associated with entrepreneurial intention, p-value